Crim 170 Research Paper 2 - Rosas, Jennifer Alvarez
There are many inquiries about whether ones race and/or gender influence their fear of and risk of being sexually assaulted. Adequate information regarding sexual assault on college campuses is readily available through the Uniform Crime Report (UCR). However, the UCR only has data on sexual assaults that have been reported, and thus not on those who did not file a formal report. The current research examined what could influence ones risk of being sexually assaulted during their college career at large western undergraduate university. Specifically examined were which gender and/or which race is more likely to experience sexual assault, including: touch without consent, attempted penetration, achieved penetration, being in a sexually abusive relationship, coerced to perform a sexual act, or any unwanted sexual act performed against them. This research also examined the participants levels of fear of experiencing any type of sexual assault between gender and race. The survey data was collected via an online convenience sample. The data indicated males and females have similar levels of fear of being sexually assaulted. However, there were some differences found between which race actually experienced sexual assault. These findings support the claim that women, specifically those who belong to a racial minority are more at risk to experience victimization in college.